IbM BISKUIT DAUN KATUK PELANCAR ASI - Erli Mutiara; Adikahriani Adikahriani; Bisrul Hapis Tambunan (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2014)
The patners for this  IbM’s activity are Female Cambodian Farmer Group and Female Farmer Group in the village of Rengas Pulau, Marelan District of Medan. The location is about 20 km away from Unimed. The objective of this activity is to provide katuk’s  flour for the production of biscuit with the application of appropriate technology to increase the farmer’s income. The implementation method for this avtivity are education, business management training, the using of oven dryer and mentoring. The output of this activity are to produce a) katuk’s flour; b) katuk’s biscuit for increasing the production of breast milk; c) katuk oven dryer. The specification of katuk oven dryer are a) oven 40×50×120cm; b) Inside material : iron plate; outside material: tin plate; shelves: iron plate; frame: iron; c)Nnumber of shelves: 6 pieces; d)Heat source : LPG (also available for electricity); e) Climate control: Auto(design for LPG); f) Drying capacity : 50 kg/hour. Results of this activity is as expected, it can be proved by the achievement of the target and the high interest and the enthusiasm of the partners when they listen to the presentation session and pay attention of the biscuit processing practices from the team leader. The production of katuk’s biscuit is ready for market thus can increase IbM’s patners income.